IMAGE ENHANCEMENT ON OBJECT DETECTION USING L0 GRADIENT PRIOR - Megawan, Sunario; Gohzali, Hernawati; Halim, Apriyanto (Kresnamedia Publisher, 2021)
Abstract Object detection is a technique used to retrieve certain parts of the image. The part can be in the form of scenery, people, or other objects. At the time of object detection, the image obtained can experience a decrease in image quality which can be caused by weather factors, namely fog, smoke, dust, rain, and others. A decrease in the quality of the image can result in errors in classification and the inability to recognize objects in the image. Therefore, the process of improving image quality becomes very important to do at the pre-processing stage in detecting image objects. The focus of the problem to be solved in this study is the return of a blurred image using L0 Gradient Prior. The results showed that the application of L0 Gradient Prior in restoring a blurred image can increase the number of objects that can be detected by the object detection system.